Analyzing aggregate environmental monitoring data for Listeria spp. in frozen food manufacturing environments. (May 2022) - Magdovitz, Brittany F.; Gummalla, Sanjay; Garren, Donna; Thippareddi, Harshavardhan; Berrang, Mark E.; Love, Kim; Harrison, Mark A.
Abstract: Food processors face serious challenges due to the ubiquity and prevalence of Listeria monocytogenes in production and processing facilities. Environmental monitoring for Listeria within the industry is important and detection of Listeria spp. is often used as an indicator for the potential presence of L. monocytogenes in the food processing environment. Environmental monitoring data from the frozen food manufacturing industry was compiled and analyzed to evaluate the adequacy of current practices in mitigating risks of L. monocytogenes in the processing environment and to determine if there are trends that could be used to further refine industry practices. A method to collect anonymous data for analysis to build a strong aggregate data set from multiple facilities was used. Information included general descriptions of each facility and specific information about individual environmental monitoring test results from environmental zones 2–4, or nonfood contact surfaces. Information collected from facilities included the size of the facilities and how environmental monitoring samples were collected and analyzed. For each individual sample, information collected included the area or equipment sampled and the result of each sample. Descriptors were provided to allow for grouping of similar results. The data represents environmental monitoring samples that were collected between six months to a year prior to the beginning of this research. Twenty-seven facilities provided 42, 799 environmental monitoring observations. Environmental zones 3 and 4 had a higher estimated marginal probability of Listeria positive results compared to zone two for routine environmental monitoring samples (p < 0.05). Pre-lethality and post-lethality production areas had a higher probability of Listeria positive results compared to lethality areas for all environmental samples (p < 0.05). Cold storage locations, i.e., coolers and freezers had a significantly higher probability for a Listeria positive result than noncold storage areas (p < 0.01). Applying statistical modeling and comparing estimated marginal probabilities of aggregate Listeria prevalence data from processing operations across the industry can provide information for guidance on focusing sanitation within processing operations to reduce risk related to L. monocytogenes. These data help to identify common themes in the industry and determine potential areas on which to focus when testing for prevalence of Listeria spp. within the food processing environment. This study serves as a useful baseline for continued improvement in environmental monitoring across all frozen food manufacturing facilities. Highlights: Environmental monitoring samples from frozen food facilities were collected. Twenty-seven facilities provided 42, 799 environmental monitoring observations. Zones 3/4 had a higher probability of Listeria positive results compared to zone 2.